A Multidimensional Study of Absorptive Capacity and Innovation Capacity and Their Impact on Business Performance - Sancho-Zamora, Rafael; Gutiérrez-Broncano, Santiago; Hernández-Perlines, Felipe; Peña-García, Isidro (Frontiers in Psychology, 2021)
The aim of this paper is to understand how absorptive capacity and innovativeness influence business performance. Most previous studies do not consider the different dimensions that both absorptive capacity and innovativeness have. And therefore, they do not analyze the relationships between these dimensions such as potential and realized absorptive capacity and product and process innovation. In our study we analyzed the relationships between each of these dimensions and the effect they have on organizational performance. To achieve this, in addition to a theoretical foundation of the working hypotheses, a questionnaire was sent to 800 CEOs of Spanish companies in different sectors, obtaining a response rate of 38.25%. Structural equation modelling was applied to test the hypothesis. Finally, this study confirms the positive effect that absorptive capacity has on innovation capacity and this in turn on business performance. Moreover, different dimensions of both absorptive capacity and innovativeness play an important role in these relationships. Future research should further study the inner workings of each of the dimensions analyzed to determine the importance of each dimension on business performance. This study contributes to a better understanding of how potential and realized absorptive capacity influence the innovativeness of firms in both their ability to innovate products and improve business processes. In addition, it explores how these different innovations impact on business performance and provide the firm with knowledge on how to invest its resources to increase profits.